Denmark : 2010 Article IV Consultation-Staff Report; Informational Annex; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Denmark. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
Denmark's flexicurity model has performed well during the crisis. The actions and the improvement in economic conditions have restored overall stability to the banking system. Private consumption has been dented by the decline in housing prices and net household wealth. Exports have rebounded, led by a reversal in the services account. Labor market policies should refocus on labor supply pressures. Additional action should be taken to further bolster financial sector stability. Policies need to focus on putting growth on a steady and sustainable path while reducing vulnerabilities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet